Functional characterization of NTRK1 mutations identified in melanoma. Issue 10 (26th June 2014) - Miranda, Claudia; Mazzoni, Mara; Sensi, Marialuisa; Pierotti, Marco A.; Greco, Angela
<x xml:space="preserve">Abstract</x> Cutaneous melanoma is the most aggressive form of skin cancer, with a complex and heterogeneous aetiology. Deregulation of the mitogen activated protein kinase cascade is common in melanoma, due to activating mutations in the BRAF and NRAS genes. Genetic studies and high‐throughput screening technologies have recently identified several somatic mutations affecting different receptor tyrosine kinase (RTK) genes. For the majority of these, however, the contribution to the complexity of melanoma biology has not been assessed. Among these, two novel missense somatic mutations (M379I and R577G) have recently been identified in the gene encoding the neurotrophic RTK NTRK1. The NTRK1 melanoma‐associated point mutations were introduced in a NTRK1 expression plasmid. Functional characterization of mutants was assessed after transient and stable transfection in HeLa and NIH3T3 cells, respectively. We showed that M379I and R577G NTRK1 receptors do not display the kinase as constitutively activated and are functionally indistinguishable from the wild‐type NTRK1 receptor. Our results indicate that a causative role for M379I and R577G NTRK1 mutations in melanoma development is highly unlikely. This supports the issue that, in parallel to systematic large scale cancer genome screening, functional studies are required to distinguish between mutations that play a causative role in tumor development and others that may only be passenger changes. © 2014 Wiley Periodicals, Inc.